A silicon material, a method of making the same, uses thereof, and devices using the same

CN114590810BActive Publication Date: 2026-11-03THE NAT CENT FOR NANOSCI & TECH NCNST OF CHINA
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202011410613.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2020-12-04
Publication Date
2026-11-03
Estimated Expiration
2040-12-04

AI Technical Summary

Technical Problem

Existing silicon materials are structurally unstable in lithium-ion batteries due to volume changes, which affects charge-discharge efficiency and cycle performance. Furthermore, existing nanostructuring methods usually sacrifice specific capacity by weight, which limits the improvement of energy density, and the preparation process is complex and costly.

Method used

The flower cluster structure silicon material is formed by interconnected wavy silicon nanosheets to form flower cluster-shaped silicon microparticles through melt mixing and low-pressure heat treatment. Combined with a simple preparation method, it achieves structural self-stability and efficient lithium-ion transport.

Benefits of technology

It improves the structural stability of silicon materials during volume changes and the lithium-ion diffusion path, enhances electron transport efficiency, increases the tap density of the material and the charge/discharge specific capacity and cycle stability of the battery, and is low in cost and can be mass-produced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114590810B_ABST
    Figure CN114590810B_ABST
Patent Text Reader

Abstract

The application provides a silicon material and a preparation method, use and device thereof. The silicon material comprises flower cluster-shaped silicon microparticles which are formed by interconnection of wavy silicon nanosheets. The method comprises: 1) mixing a silicon source and a lithium source under an inert atmosphere to obtain a molten product; and 2) heat-treating the molten product under a low pressure and a non-oxidizing atmosphere to obtain the silicon material. In the silicon material, the wavy two-dimensional silicon nanosheets have a stress self-release characteristic, which not only improves the self-stability of the structure and interface of silicon in the volume change process, but also greatly shortens the diffusion path of lithium ions; the flower cluster-shaped microporous structure not only facilitates efficient transmission of electrons and low tortuosity transportation of lithium ions, but also improves the tap density of the material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of materials technology and relates to a silicon material, its preparation method, uses, and apparatus for using the same. Background Technology

[0002] To meet the ever-growing energy demands of portable electronic devices and electric vehicles, there has been a continuous pursuit of higher energy densities in lithium-ion rechargeable batteries. However, graphite, as the most commonly used anode material, has a relatively low theoretical capacity, failing to meet these requirements. Historically, every breakthrough in energy density in lithium-ion battery development has been driven by the development of new electrode materials. Therefore, there is an urgent need for new anode materials that can provide higher energy densities, longer cycle lives, and safe discharge / charge potentials.

[0003] Among all possible anode material candidates, silicon stands out due to its abundant natural resources, low cost, and large reversible capacity (4200 mAh / g), achieved through an alloying-dealloying reaction with lithium at an ideal operating potential. However, silicon materials undergo significant volume changes (over 300%) during charge and discharge, and the resulting mechanical stress leads to pulverization and structural collapse of the active material, as well as detachment between the material and the current collector, resulting in rapid capacity decay and reduced battery cycle performance. Furthermore, due to this volume expansion effect, silicon struggles to form a stable solid electrolyte interphase (SEI) film in the electrolyte, leading to reduced charge and discharge efficiency and further accelerating the deterioration of cycle performance.

[0004] Currently, in order to solve the problems mentioned above, the construction of silicon-carbon nanocomposites by nanostructuring, porousing, and / or combining silicon materials with carbon nanomaterials can, to some extent, solve the structural and interface instability problems caused by the volume expansion effect of silicon during charging and discharging, thereby improving its charging, discharging, and cycling performance.

[0005] However, it is worth noting that, on the one hand, the improvement of cycle stability through nanostructuring of silicon materials (such as zero-dimensional silicon nanoparticles, one-dimensional silicon nanowires or nanotubes, and three-dimensional porous silicon) often comes at the cost of sacrificing the material's specific capacity. On the other hand, these structural methods typically lead to a significant reduction in the tap density of the active material, severely limiting its volumetric capacity and energy density, and hindering its practical application in batteries and / or related energy storage systems. Current micro / nanostructuring can improve the tap density of silicon or silicon-carbon composites to some extent, but it is still mainly based on zero-dimensional, one-dimensional, and / or three-dimensional porous silicon, failing to achieve a synergistic improvement in cycle stability and specific capacity. Furthermore, micro / nanostructuring primarily relies on expensive commercial silicon nanoparticles, highly hazardous gaseous silicon sources such as silane, environmentally unfriendly etching processes such as hydrofluoric acid, or demanding (e.g., ultra-high vacuum, ultra-high temperature), energy-intensive, and complex synthesis processes. Therefore, both the materials and methods themselves severely limit the performance and practical application of existing micro / nanostructured silicon and silicon-carbon composites.

[0006] CN105789577A discloses a method for preparing a silicon anode material for lithium-ion batteries and the silicon anode material itself, specifically including the following steps: Step 1, surface hydroxylation: Silicon suboxide is placed in a mixed solution of ammonia, hydrogen peroxide, and water, heated to boiling, and stirred for 10-60 min, then washed with water, filtered, and vacuum dried at 80-120℃ for 2-12 h; Step 2, stirring: The dried product from Step 1 is placed in an anhydrous ethanol solution containing a titanium source and stirred for 2-10 h; then water is added and stirred for 15-75 min, followed by the addition of graphite, then an anhydrous ethanol solution containing a lithium source, and finally glacial acetic acid is added and stirred until the black sol becomes a gel; Step 3, aging and drying: The gel generated in Step 2 is aged for 12 h or more, and then vacuum dried at 70-90℃ for 8-16 h; Step 4, calcination: The gel after aging and drying in Step 3 is broken up and calcined under an inert atmosphere; finally, it is cooled to room temperature to obtain the silicon anode material. However, the products obtained by this method still need further improvement in terms of charge-discharge specific capacity and cycle stability.

[0007] Therefore, finding a silicon material that combines excellent electronic and lithium-ion transport properties with structural / interface stability, and that is simple to prepare, energy-efficient, scalable, and inexpensive is an urgent problem to be solved. Summary of the Invention

[0008] In view of the above-mentioned steps in the prior art, the purpose of this invention is to provide a silicon material, its preparation method, uses, and an apparatus for using the same. The silicon material provided by this invention is a flower cluster structure silicon material, which is very suitable as a negative electrode active material for lithium-ion batteries, and the resulting batteries have extremely excellent charge-discharge specific capacity and cycle stability.

[0009] To achieve this objective, the present invention adopts the following technical solution:

[0010] In a first aspect, the present invention provides a silicon material comprising flower-like silicon microparticles formed by interconnected wavy silicon nanosheets.

[0011] The silicon material provided by this invention is a flower-cluster silicon material, in which two-dimensional wavy silicon nanosheets are interconnected to form flower-cluster silicon microparticles. Compared with common zero-dimensional, one-dimensional, three-dimensional, and / or flat two-dimensional silicon nanosheets, these wavy two-dimensional silicon nanosheets have stress self-releasing characteristics, which not only improves the self-stability of silicon structure and interface during volume changes, but also greatly shortens the diffusion path of lithium ions; the flower-cluster microstructure not only facilitates efficient electron transport and low-torsion lithium ion transport, but also improves the tap density of the material.

[0012] The following are preferred technical solutions of the present invention, but are not intended to limit the technical solutions provided by the present invention. The technical objectives and beneficial effects of the present invention can be better achieved and realized through the following preferred technical solutions.

[0013] As a preferred embodiment of the present invention, the particle size of the flower-shaped silicon microparticles is 1-50 μm, such as 1 μm, 5 μm, 10 μm, 20 μm, 30 μm, 40 μm, or 50 μm. In this invention, if the particle size of the flower-shaped silicon microparticles is too large, lithium-ion transport will be hindered, which is not conducive to capacity utilization and stability improvement. If the particle size of the flower-shaped silicon microparticles is too small, the tap density will be low, reducing the volumetric energy density.

[0014] Preferably, the thickness of the wavy silicon nanosheet is 1-100 nm, such as 1 nm, 10 nm, 30 nm, 50 nm, 70 nm or 100 nm.

[0015] In a second aspect, the present invention provides a method for preparing a silicon material as described in the first aspect, the method comprising the following steps:

[0016] (1) The silicon source and the lithium source are melted and mixed under an inert atmosphere to obtain a molten product;

[0017] (2) The molten product of step (1) is heat-treated under low pressure and non-oxidizing atmosphere to obtain the silicon material.

[0018] In the preparation method provided by the present invention, the melting and mixing process in step (1) will undergo an alloying reaction to form a silicon-lithium alloy, while the low-pressure heat treatment in step (2) is a process of pyrolysis of the silicon-lithium alloy, which separates the silicon and lithium in the silicon-lithium alloy and forms a flower-like silicon material.

[0019] In this invention, the lithium source is used to restructure silicon microparticles to obtain flower-like silicon.

[0020] In step (2), the purpose of using low-pressure conditions is to pyrolyze the silicon-lithium alloy within the temperature range to achieve the preparation of flower cluster structure silicon.

[0021] The preparation method of the present invention is not only low in cost, simple in process, and low in energy consumption, but also can be mass-produced.

[0022] As a preferred technical solution of the present invention, the silicon source in step (1) includes silicon microparticles.

[0023] Preferably, the silicon microparticles include crystalline silicon microparticles and / or amorphous silicon microparticles.

[0024] Preferably, the particle size of the silicon source in step (1) is 1-40 μm, such as 1 μm, 5 μm, 10 μm, 15 μm, 20 μm, 30 μm or 40 μm.

[0025] Preferably, the lithium source in step (1) includes any one or a combination of at least two of lithium metal powder, lithium metal flakes, or lithium metal foil.

[0026] Preferably, the mass ratio of silicon source to lithium source in step (1) is 1:10-10:1, such as 1:10, 1:5, 1:1, 5:1, or 10:1. In this invention, if there is too much silicon source, some silicon raw material will remain, and the flower-like silicon structure cannot be completely formed; if there is too much lithium source, it will lead to unnecessary waste of resources, because the alloying reaction between lithium and silicon will reach saturation to a certain extent.

[0027] Preferably, the inert atmosphere in step (1) includes any one or a combination of at least two of argon, helium or neon atmospheres.

[0028] As a preferred embodiment of the present invention, the melt mixing in step (1) is carried out under normal pressure. Normal pressure means that the process is carried out under atmospheric pressure without any pressurization or depressurization.

[0029] Preferably, the melting and mixing temperature in step (1) is 180-400℃, such as 180℃, 200℃, 250℃, 300℃, 350℃, or 400℃. In this invention, if the melting and mixing temperature is too high, it will lead to unnecessary energy consumption and resource waste, because lithium and silicon can be fully alloyed within this temperature range; if the melting and mixing temperature is too low, it will be below the melting temperature of lithium, and the alloying reaction with silicon cannot be fully carried out.

[0030] Preferably, the melting and mixing time in step (1) is 10 min to 12 h, such as 10 min, 30 min, 1 h, 2 h, 5 h, 10 h or 12 h, and preferably 30 min to 6 h.

[0031] As a preferred technical solution of the present invention, the pressure of the low pressure in step (2) is <100kPa, such as 90kPa, 80kPa, 70kPa, 60kPa, 50kPa, 40kPa, 30kPa, 20kPa or 10kPa, etc., preferably 10-50kPa;

[0032] Preferably, the non-oxidizing atmosphere in step (2) is any one or at least a combination of two or more of helium atmosphere, neon atmosphere, argon atmosphere or nitrogen atmosphere, and more preferably argon atmosphere and / or nitrogen atmosphere.

[0033] Preferably, the heat treatment temperature in step (2) is 400-1000℃, such as 400℃, 500℃, 600℃, 700℃, 800℃, 900℃, or 1000℃, and more preferably 600-900℃. In this invention, if the heat treatment temperature in step (2) is too high, it will directly cause the silicon wafer layers to fuse and adhere to each other to form a solid structure, preventing the formation of a flower cluster structure, and significantly reducing the lithium storage performance; if the heat treatment temperature in step (2) is too low, it will lead to incomplete pyrolysis of the silicon-lithium alloy, generating a large number of by-products, which seriously reduces the material capacity.

[0034] Preferably, the heat treatment time in step (2) is 0.5-24h, such as 0.5h, 1h, 2h, 6h, 12h, 18h or 24h, and preferably 0.5-12h.

[0035] As a preferred technical solution of the present invention, step (2) further includes: cleaning the heat-treated product to remove byproducts.

[0036] Preferably, the cleaning includes solvent cleaning and water cleaning.

[0037] Preferably, the solvent is an inorganic solvent or an organic solvent.

[0038] Preferably, the inorganic solvent includes any one or a combination of at least two of hydrochloric acid, sulfuric acid, nitric acid, and phosphoric acid.

[0039] Preferably, the organic solvent includes any one or a combination of at least two of methanol, ethanol, ethylene glycol, isopropanol, acetone, acetic acid, acetonitrile, tetrahydrofuran, dimethylformamide, and N-methylpyrrolidone.

[0040] As a further preferred embodiment of the preparation method described in this invention, the method includes the following steps:

[0041] (1) Silicon microparticles and metallic lithium are melt-mixed at 180-400℃ under normal pressure and inert atmosphere for 10 min-12 h to obtain a melt product;

[0042] (2) The molten product obtained in step (1) is heat-treated at 400-1000℃ for 0.5-24h under a pressure of <100kPa and a non-oxidizing atmosphere to obtain the heat-treated product;

[0043] (3) The product of the heat treatment in step (2) is subjected to solvent cleaning and water cleaning to remove byproducts, and the silicon material is obtained.

[0044] Thirdly, the present invention provides the use of the silicon material as described in the first aspect, wherein the silicon material is used as a negative electrode material for lithium-ion batteries.

[0045] The silicon material of this invention is very suitable as a negative electrode active material for lithium-ion batteries, and the resulting batteries have extremely excellent charge-discharge specific capacity and cycle stability.

[0046] Fourthly, the present invention provides an apparatus comprising the silicon material as described in the first aspect.

[0047] Preferably, the device includes a lithium-ion battery, a lithium-sulfur battery, a sodium-ion battery, an air battery, or a supercapacitor.

[0048] Compared with the prior art, the present invention has the following beneficial effects:

[0049] (1) In the flower cluster structure silicon material prepared by the present invention, wavy two-dimensional silicon nanosheets are directly connected to each other to form flower cluster-shaped silicon microparticles. Compared with common zero-dimensional, one-dimensional, three-dimensional and / or flat two-dimensional silicon nanosheets, wavy two-dimensional silicon nanosheets have stress self-release characteristics, which not only improves the self-stability of silicon structure and interface during volume change, but also greatly shortens the diffusion path of lithium ions; the flower cluster-shaped microstructure not only facilitates the efficient transport of electrons and the low tortuosity transport of lithium ions, but also improves the tap density of the material.

[0050] (2) The silicon material of the present invention is very suitable as a negative electrode active material for lithium-ion batteries, and the resulting batteries have extremely excellent charge-discharge specific capacity and cycle stability. The battery prepared by the silicon material provided by the present invention can achieve an initial discharge specific capacity of 3568 mAh / g, and can achieve 215 cycles when its cycle capacity retention rate drops to 90%.

[0051] (3) The preparation method of the present invention is not only low in cost, simple in process and low in energy consumption, but also can be mass-produced. Attached Figure Description

[0052] Figure 1 The image is a scanning electron microscope (SEM) image of the silicon material provided in Example 1. Detailed Implementation

[0053] To better illustrate the present invention and facilitate understanding of its technical solutions, the present invention will be further described in detail below. However, the following embodiments are merely simplified examples of the present invention and do not represent or limit the scope of protection of the present invention. The scope of protection of the present invention is determined by the claims.

[0054] The following are typical but non-limiting embodiments of the present invention:

[0055] Example 1

[0056] Preparation of flower cluster structure silicon materials:

[0057] Crystalline silicon microparticles (1-5 μm) and metallic lithium mixed in a 1:1 weight ratio were heated to 300 °C and held for 1 h in an argon atmosphere. Then, the mixture was heated to 650 °C in a low-pressure (90 kPa) argon atmosphere and held for 2 h. After cooling, the product was washed with ethanol and water to remove lithium-containing byproducts, and then the flower cluster structure silicon material was obtained.

[0058] Figure 1 This is a scanning electron microscope image of the silicon material prepared in this embodiment. As can be seen from the image, the flower-like silicon microparticles are composed of interconnected wavy two-dimensional silicon nanosheets, and have a flower-like structure.

[0059] The silicon material prepared in this embodiment includes flower-shaped silicon microparticles composed of interconnected wavy silicon nanosheets. The particle size of the flower-shaped silicon microparticles is 1-6 μm, and the thickness of the wavy silicon nanosheets is 1-10 nm.

[0060] Preparation of negative electrode:

[0061] Using the flower cluster structure silicon material of this embodiment as the negative electrode active material, the negative electrode active material, the binder polyvinylidene fluoride (PVDF), and the conductive agent acetylene black are uniformly mixed in N-methylpyrrolidone (NMP) to prepare a slurry, which is then coated on a copper foil current collector and vacuum dried at 120°C for 12 hours before being rolled into a negative electrode sheet.

[0062] Battery fabrication:

[0063] Using a negative electrode as the test electrode and a lithium metal foil as the counter electrode, the electrolyte was 1M LiPF6 / EC:DEC (1:1; v / v) with added FEC, which is a mixed solvent of ethylene carbonate and diethyl carbonate containing dissolved lithium hexafluorophosphate. The separator was Celgard 2400. A button-type lithium-ion battery was assembled in a glove box with oxygen and water content of less than 1 ppm.

[0064] Example 2

[0065] Preparation of flower cluster structure silicon materials:

[0066] Crystalline silicon microparticles (5-10 μm) and metallic lithium mixed in a 3:2 weight ratio were heated to 250 °C and held for 2 h under an argon atmosphere. Then, the mixture was heated to 700 °C under a low-pressure (80 kPa) nitrogen atmosphere and held for 1 h. The cooled product was washed with ethylene glycol and water to remove lithium-containing byproducts (such as lithium nitride) to obtain a flower cluster structure silicon material.

[0067] The silicon material prepared in this embodiment includes flower-shaped silicon microparticles composed of interconnected wavy silicon nanosheets. The particle size of the flower-shaped silicon microparticles is 8-15 μm, and the thickness of the wavy silicon nanosheets is 10-20 nm.

[0068] Preparation of negative electrode:

[0069] Using the flower cluster structure silicon material of this embodiment as the negative electrode active material, the negative electrode active material, binder polyacrylic acid (KPAA) and conductive agent carbon black are uniformly mixed in water to prepare a slurry, which is then coated on a copper foil current collector, vacuum dried at 100°C for 12 hours and then rolled to form a negative electrode sheet.

[0070] Battery fabrication:

[0071] Using a negative electrode as the test electrode and a lithium metal foil as the counter electrode, the electrolyte was 1M LiPF6 / EC:DEC (1:1; v / v) with added FEC, which is a mixed solvent of ethylene carbonate and diethyl carbonate containing dissolved lithium hexafluorophosphate. The separator was Celgard 2400. A button-type lithium-ion battery was assembled in a glove box with oxygen and water content of less than 1 ppm.

[0072] Example 3

[0073] Preparation of flower cluster structure silicon materials:

[0074] Crystalline silicon microparticles (5-10 μm) and metallic lithium mixed in a 6:5 weight ratio were heated to 400 °C and held for 30 min under an argon atmosphere. Then, the mixture was heated to 600 °C under a low-pressure (50 kPa) helium atmosphere and held for 4 h. After cooling, the product was washed with isopropanol and water to remove lithium-containing byproducts, and then the flower cluster structure silicon material was obtained.

[0075] The silicon material prepared in this embodiment includes flower-shaped silicon microparticles composed of interconnected wavy silicon nanosheets. The particle size of the flower-shaped silicon microparticles is 8-15 μm, and the thickness of the wavy silicon nanosheets is 20-30 nm.

[0076] Preparation of negative electrode:

[0077] Using the flower cluster structure silicon material of this embodiment as the negative electrode active material, the negative electrode active material, the binder sodium alginate and the conductive agent carbon black are uniformly mixed in water to prepare a slurry, which is then coated on a copper foil current collector and rolled into a negative electrode sheet after being vacuum dried at 100°C for 12 hours.

[0078] Battery fabrication:

[0079] Using a negative electrode as the test electrode and a lithium metal foil as the counter electrode, the electrolyte was 1M LiPF6 / EC:DEC (1:1; v / v) with added FEC, which is a mixed solvent of ethylene carbonate and diethyl carbonate containing dissolved lithium hexafluorophosphate. The separator was Celgard 2400. A button-type lithium-ion battery was assembled in a glove box with oxygen and water content of less than 1 ppm.

[0080] Example 4

[0081] Preparation of flower cluster structure silicon materials:

[0082] Amorphous silicon microparticles (D50 of 5 μm) and metallic lithium were mixed in a 3:5 weight ratio under a helium atmosphere, heated to 350 °C and held for 1.5 h. Then, the mixture was heated to 800 °C under a low-pressure (10 kPa) nitrogen atmosphere and held for 30 min. After cooling, the product was washed with hydrochloric acid and water to remove lithium-containing byproducts (such as lithium nitride) to obtain a flower cluster structure silicon material.

[0083] The silicon material prepared in this embodiment includes flower-shaped silicon microparticles composed of interconnected wavy silicon nanosheets. The particle size of the flower-shaped silicon microparticles is 6-8 μm, and the thickness of the wavy silicon nanosheets is 30-45 nm.

[0084] Preparation of negative electrode:

[0085] Using the flower cluster structure silicon material of this embodiment as the negative electrode active material, the negative electrode active material, the binder polyvinylidene fluoride (PVDF), and the conductive agent acetylene black are uniformly mixed in N-methylpyrrolidone (NMP) to prepare a slurry, which is then coated on a copper foil current collector and vacuum dried at 120°C for 12 hours before being rolled into a negative electrode sheet.

[0086] Battery fabrication:

[0087] Using a negative electrode as the test electrode and a lithium metal foil as the counter electrode, the electrolyte was 1M LiPF6 / EC:DEC (1:1; v / v) with added FEC, which is a mixed solvent of ethylene carbonate and diethyl carbonate containing dissolved lithium hexafluorophosphate. The separator was Celgard 2400. A button-type lithium-ion battery was assembled in a glove box with oxygen and water content of less than 1 ppm.

[0088] Example 5

[0089] Preparation of flower cluster structure silicon materials:

[0090] Crystalline silicon microparticles (15-25 μm) and metallic lithium were mixed in a 1:10 weight ratio under an argon atmosphere, heated to 180 °C and held for 12 h. Then, the mixture was heated to 400 °C under a low-pressure (50 kPa) helium atmosphere and held for 12 h. After cooling, the product was washed with isopropanol and water to remove lithium-containing byproducts, thus obtaining a flower cluster structure silicon material.

[0091] The silicon material prepared in this embodiment includes flower-shaped silicon microparticles composed of interconnected wavy silicon nanosheets. The particle size of the flower-shaped silicon microparticles is 15-30 μm, and the thickness of the wavy silicon nanosheets is 45-70 nm.

[0092] Preparation of negative electrode:

[0093] Using the flower cluster structure silicon material of this embodiment as the negative electrode active material, the negative electrode active material, the binder sodium alginate and the conductive agent carbon black are uniformly mixed in water to prepare a slurry, which is then coated on a copper foil current collector and rolled into a negative electrode sheet after being vacuum dried at 100°C for 12 hours.

[0094] Battery fabrication:

[0095] Using a negative electrode as the test electrode and a lithium metal foil as the counter electrode, the electrolyte was 1M LiPF6 / EC:DEC (1:1; v / v) with added FEC, which is a mixed solvent of ethylene carbonate and diethyl carbonate containing dissolved lithium hexafluorophosphate. The separator was Celgard 2400. A button-type lithium-ion battery was assembled in a glove box with oxygen and water content of less than 1 ppm.

[0096] Example 6

[0097] Preparation of flower cluster structure silicon materials:

[0098] Crystalline silicon microparticles (30-40 μm) and metallic lithium were mixed in a 10:1 weight ratio under an argon atmosphere and heated to 400 °C and held for 10 min. Then, the mixture was heated to 1000 °C under a low-pressure (50 kPa) helium atmosphere and held for 24 h. After cooling, the product was washed with isopropanol and water to remove lithium-containing byproducts, and then the flower cluster structure silicon material was obtained.

[0099] The silicon material prepared in this embodiment includes flower-shaped silicon microparticles composed of interconnected wavy silicon nanosheets. The particle size of the flower-shaped silicon microparticles is 30-50 μm, and the thickness of the wavy silicon nanosheets is 75-100 nm.

[0100] Preparation of negative electrode:

[0101] Using the flower cluster structure silicon material of this embodiment as the negative electrode active material, the negative electrode active material, the binder sodium alginate and the conductive agent carbon black are uniformly mixed in water to prepare a slurry, which is then coated on a copper foil current collector and rolled into a negative electrode sheet after being vacuum dried at 100°C for 12 hours.

[0102] Battery fabrication:

[0103] Using a negative electrode as the test electrode and a lithium metal foil as the counter electrode, the electrolyte was 1M LiPF6 / EC:DEC (1:1; v / v) with added FEC, which is a mixed solvent of ethylene carbonate and diethyl carbonate containing dissolved lithium hexafluorophosphate. The separator was Celgard 2400. A button-type lithium-ion battery was assembled in a glove box with oxygen and water content of less than 1 ppm.

[0104] Example 7

[0105] The difference between this embodiment and Example 3 in the method for preparing flower cluster structure silicon material is that the temperature is raised to 1020°C under a low-pressure helium atmosphere. Otherwise, the method for preparing flower cluster structure silicon material is the same as in Example 3.

[0106] The silicon material prepared in this embodiment is mainly composed of an irregular solid silicon structure, containing a very small amount of flower-like silicon composed of interconnected wavy silicon nanosheets, and the particle size of the silicon micron particles is 8-15 μm.

[0107] The method for preparing the negative electrode and the battery in this embodiment is the same as that in Example 3, but the negative electrode active material used is the silicon material provided in this embodiment.

[0108] Example 8

[0109] The difference between this embodiment and Example 3 in the method for preparing flower cluster structure silicon material is that the temperature is raised to 380°C under a low-pressure helium atmosphere. Otherwise, the method for preparing flower cluster structure silicon material is the same as in Example 3.

[0110] The silicon material prepared in this embodiment includes flower-like silicon micron particles composed of interconnected wavy silicon nanosheets. The particle size of the micron silicon is 8-15 μm. However, the silicon material also contains structures that are not formed by interconnected wavy silicon nanosheets and contains a large number of non-elemental silicon byproducts.

[0111] The method for preparing the negative electrode and the battery in this embodiment is the same as that in Example 3, but the negative electrode active material used is the silicon material provided in this embodiment.

[0112] Comparative Example 1

[0113] The difference between this comparative example and Example 4 in the method of preparing silicon material is that: commercial amorphous silicon microparticles (D50 of 5 μm) and metallic lithium are mixed and heated directly to 800°C under a low-pressure (10 kPa) nitrogen atmosphere and held for 30 min. After cooling, the product is washed with hydrochloric acid and water to remove lithium-containing byproducts (such as lithium nitride) to obtain silicon material.

[0114] That is, the product obtained in this comparative example did not undergo a melt-mixing process during preparation.

[0115] The method for preparing the negative electrode and the battery in this embodiment is the same as that in Example 4, but the negative electrode active material used is the silicon material provided in this embodiment.

[0116] Test methods

[0117] For the batteries provided in each embodiment and comparative example, the initial charge-discharge capacity was tested under 0.05C charge / 0.05C discharge conditions; the number of cycles when the cycle capacity retention rate decreased to 90% was tested under 0.5C charge / 0.5C discharge conditions. The test results are shown in the table below.

[0118] Table 1

[0119]

[0120] Based on the above embodiments and comparative examples, it can be seen that in the flower-cluster structure silicon materials prepared in Examples 1-6, the wavy two-dimensional silicon nanosheets are directly connected to each other to form flower-cluster silicon microparticles. The wavy two-dimensional silicon nanosheets have stress self-releasing characteristics, which not only improves the self-stability of the structure and interface of silicon during volume changes, but also greatly shortens the diffusion path of lithium ions. The flower-cluster microstructure not only facilitates the efficient transport of electrons and the low tortuosity transport of lithium ions, but also improves the tap density of the material. This makes the silicon materials provided in Examples 1-6 have extremely excellent charge-discharge specific capacity and cycle stability after being fabricated into batteries.

[0121] In Example 7, the high temperature of the heat treatment under low pressure after melting and mixing caused some silicon wafer layers to fuse and stick together to form a solid particle structure instead of a flower cluster structure, resulting in a decrease in lithium storage stability.

[0122] In Example 8, because the heat treatment temperature under low pressure after melting and mixing was too low, most of the silicon material could not form a flower-like structure, and a large number of by-products were introduced, resulting in reduced capacity and poor stability.

[0123] Comparative Example 1 failed to achieve improved lithium storage performance because the silicon structure could not be reorganized and the flower cluster structure was not formed during the preparation process without melt mixing.

[0124] The applicant declares that the detailed process equipment and process flow of the present invention are illustrated through the above embodiments, but the present invention is not limited to the above detailed process equipment and process flow, that is, it does not mean that the present invention must rely on the above detailed process equipment and process flow to be implemented. Those skilled in the art should understand that any improvements to the present invention, equivalent substitutions of the raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the scope of protection and disclosure of the present invention.

Claims

1. A silicon material, characterized in that, The silicon material includes flower-like silicon microparticles composed of interconnected wavy silicon nanosheets. The silicon material is obtained by the following preparation method, which includes: (1) Silicon source and lithium source are melted and mixed under an inert atmosphere to undergo an alloying reaction and obtain silicon-lithium alloy; (2) The silicon-lithium alloy described in step (1) is heat-treated under low pressure and non-oxidizing atmosphere to obtain the silicon material. The heat treatment temperature in step (2) is 400-1000℃.

2. The silicon material according to claim 1, characterized in that, The flower-like silicon microparticles have a particle size of 1-50 μm.

3. The silicon material according to claim 1, characterized in that, The thickness of the wavy silicon nanosheets is 1-100 nm.

4. A method for preparing the silicon material as described in any one of claims 1-3, characterized in that, The preparation method includes the following steps: (1) Silicon source and lithium source are melted and mixed under an inert atmosphere to undergo an alloying reaction and obtain silicon-lithium alloy; (2) The silicon-lithium alloy described in step (1) is heat-treated under low pressure and non-oxidizing atmosphere to obtain the silicon material. The heat treatment temperature in step (2) is 400-1000℃.

5. The preparation method according to claim 4, characterized in that, The silicon source in step (1) includes silicon microparticles.

6. The preparation method according to claim 5, characterized in that, The silicon microparticles include micron-sized crystalline silicon and / or amorphous silicon.

7. The preparation method according to claim 4, characterized in that, The silicon source in step (1) has a particle size of 1-40 μm.

8. The preparation method according to claim 4, characterized in that, The lithium source in step (1) includes any one or a combination of at least two of lithium metal powder, lithium metal flakes or lithium metal foil.

9. The preparation method according to claim 4, characterized in that, The mass ratio of silicon source to lithium source in step (1) is 1:10-10:

1.

10. The preparation method according to claim 4, characterized in that, The inert atmosphere in step (1) includes any one or a combination of at least two of the following: argon atmosphere, helium atmosphere, or neon atmosphere.

11. The preparation method according to claim 4, characterized in that, The melt mixing in step (1) is carried out under normal pressure.

12. The preparation method according to claim 4, characterized in that, The melting and mixing temperature in step (1) is 180-400℃.

13. The preparation method according to claim 4, characterized in that, The melting and mixing time in step (1) is 10 min to 12 h.

14. The preparation method according to claim 13, characterized in that, The melting and mixing time in step (1) is 30 min to 6 h.

15. The preparation method according to claim 4, characterized in that, The pressure of the low pressure in step (2) is <100kPa.

16. The preparation method according to claim 15, characterized in that, The low pressure mentioned in step (2) is 10-50 kPa.

17. The preparation method according to claim 4, characterized in that, The non-oxidizing atmosphere in step (2) is any one or at least a combination of two of the following: helium atmosphere, neon atmosphere, argon atmosphere, or nitrogen atmosphere.

18. The preparation method according to claim 17, characterized in that, The non-oxidizing atmosphere in step (2) is an argon atmosphere and / or a nitrogen atmosphere.

19. The preparation method according to claim 4, characterized in that, The heat treatment temperature in step (2) is 600-900℃.

20. The preparation method according to claim 4, characterized in that, The heat treatment time in step (2) is 0.5-24 hours.

21. The preparation method according to claim 20, characterized in that, The heat treatment time in step (2) is 0.5-12 hours.

22. The preparation method according to claim 4, characterized in that, Step (2) further includes: cleaning the heat-treated product to remove byproducts.

23. The preparation method according to claim 22, characterized in that, The cleaning process includes solvent cleaning and water cleaning.

24. The preparation method according to claim 23, characterized in that, The solvent is an inorganic solvent or an organic solvent.

25. The preparation method according to claim 24, characterized in that, The inorganic solvent includes any one or a combination of at least two of hydrochloric acid, sulfuric acid, nitric acid, and phosphoric acid.

26. The preparation method according to claim 24, characterized in that, The organic solvent includes any one or a combination of at least two of methanol, ethanol, ethylene glycol, isopropanol, acetone, acetic acid, acetonitrile, tetrahydrofuran, dimethylformamide, and N-methylpyrrolidone.

27. The preparation method according to claim 4, characterized in that, The preparation method includes the following steps: (1) Silicon microparticles and metallic lithium are melt-mixed at 180-400℃ under normal pressure and inert atmosphere for 10min-12h to undergo an alloying reaction and obtain silicon-lithium alloy; (2) The silicon-lithium alloy described in step (1) is heat-treated at 400-1000℃ for 0.5-24h under a pressure of <100kPa and a non-oxidizing atmosphere to obtain the heat-treated product; (3) The product of the heat treatment in step (2) is subjected to solvent cleaning and water cleaning to remove byproducts, and the silicon material is obtained.

28. The use of the silicon material according to any one of claims 1-3, characterized in that, The silicon material is used as the negative electrode material for lithium-ion batteries.

29. An apparatus, characterized in that, The device comprises the silicon material as described in any one of claims 1-3, and the device includes a lithium-ion battery, a lithium-sulfur battery, a sodium-ion battery, an air battery, or a supercapacitor.

Citation Information

Patent Citations

  • Preparation method for silicon negative electrode material for lithium ion battery and silicon negative electrode material

    CN105789577A

  • Layered material, porous structure and producing method thereof

    JP2019210194A